Teaching and learning space allocation in higher education institutions - Ishak, Mohd. Hafizal (2011)
Allocating space for teaching and learning is one of the facility management main elements in universities. Increased in the number of students, courses and programmes are the main contributing factors that generate teaching and learning space allocation. Lack of management will reduce the effectiveness of teaching and learning process. The faculty’s administration also does not have any computerized system that may help deliver information about teaching and learning space. A computerized system is needed for space allocation information to help the faculty to make good decisions. Thus, this research has three objectives. The first objective is to develop a conceptual framework for teaching and learning space allocation according to user’s requirements. The second objective is to develop a prototype system for teaching and learning space allocation information based on the conceptual framework of user’s requirements. The final objective is to test run the system based on the user’s requirements analysis. In developing the prototype system, firstly, this research analyses user’s requirements in teaching and learning space allocation. Next was the process for developing the system consisting of data management, analysis and presentation of teaching and learning space allocation information system. Finally, the system underwent a test run incorporating user’s teaching and learning requirement that has been determined earlier. In conclusion, the system is capable of helping the faculty’s administration in delivering the information about teaching and learning space as systematic manner. Recommendations for future research includes consideration of other aspects of user’s requirements of teaching and learning facilities, system’s technical improvement, method of determining the user’s requirements and more advanced spatial analysis for development of a better system.